THE INFLUENCE OF LIVELIHOOD VULNERABILITY INDEX ON THE IMPACT OF MELON FARMING RISKS IN KAYULEMAH VILLAGE SUMBERREJO SUB DISTRICT BOJONEGORO REGENCY - Hamdayyuwaafi, M. Wildan; Rosihan Asmara; Dwi Retno Andriani (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Melon farming has been engaged by farmers in Kayulemah Village since a dozen years ago. Small land tenure makes melon farming as solution to improve the welfare of farmers through greater profits when compared to rice farming with the same land area. Profit maximization can be maintained and increased through the utilization of farmers' livelihood assets which are used as a basis for consideration in handling and controlling the risks of farming businesses that will be faced. The purpose of this research is to determine the influence between the level of vulnerability from livelihood assets to the impact of farming risks experienced. The location of the research was determined purposely and the samples were taken using the probability sampling method which was carried out randomly (simple random sampling) which resulted in 76 people as samples from a total of 325 melon farmers. This research data uses primary data and secondary data which is processed using SEM-PLS analysis using SmartPLS 4.1.0.3 which shows the positive direction of the significant influence of the level of vulnerability on the impact of farming risks experienced by farmers.